2009
DOI: 10.4049/jimmunol.0901187
|View full text |Cite
|
Sign up to set email alerts
|

c-Myb Is Required for Pro-B Cell Differentiation

Abstract: The c-Myb transcription factor is required for normal adult hematopoiesis. However, the embryonic lethality of Myb-null mutations has been an impediment to identifying roles for c-Myb during lymphocyte development. We have used tissue-specific inactivation of the Myb locus in early progenitor cells to demonstrate that c-Myb is absolutely required for the differentiation of CD19+ B-lineage cells and B cell differentiation is profoundly blocked beyond the pre-pro-B cell stage in Mybf/f Mb1-cre mice. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 64 publications
7
64
0
Order By: Relevance
“…BrdU decay experiments revealed that this analog persisted in 19 + 45R lo BrdU + cells for ∼1 m after cessation the injections, which indicates that following one or several rounds of division, these cells remain in G 0 phase, favoring their final differentiation. In support of this hypothesis, we observed strong cmyb and weak Notch2 transcription, genes implicated in the transcriptional profile of highly differentiated B cells (42 (44). BCR ligation with anti-IgM had no effect on 19 + 45R lo cells, despite their expression of IgM.…”
Section: Discussionsupporting
confidence: 68%
“…BrdU decay experiments revealed that this analog persisted in 19 + 45R lo BrdU + cells for ∼1 m after cessation the injections, which indicates that following one or several rounds of division, these cells remain in G 0 phase, favoring their final differentiation. In support of this hypothesis, we observed strong cmyb and weak Notch2 transcription, genes implicated in the transcriptional profile of highly differentiated B cells (42 (44). BCR ligation with anti-IgM had no effect on 19 + 45R lo cells, despite their expression of IgM.…”
Section: Discussionsupporting
confidence: 68%
“…A role for c-myb in adult hematopoiesis has been shown more recently using several conditional knockout (KO) and mutant mouse models. In adult thymocytes and B lymphocytes, disruption of c-myb blocks development at the DN3 and prepro B stages, respectively (5)(6)(7)(8). c-myb expression is also required for erythropoiesis, myelopoiesis, and the development and maintenance of HSCs (9)(10)(11)(12), underscoring the importance of this gene within the entire hematopoietic compartment.…”
mentioning
confidence: 99%
“…Knockout mouse studies have demonstrated an absolute requirement for Myb/p300 in hematopoiesis and a series of elegant conditional mutant studies in mice have defined key roles for Myb in progression of erythropoiesis and lymphopoiesis (17)(18)(19). In contrast, Myb/p300 appears to play a repressive role in megakaryocytopoiesis.…”
mentioning
confidence: 99%